Power and truth in political discourse language and ideological narratives - Anastassov, Vassil Hristov (Cambridge Scholars Publishing, 2018)
The book deals with the linguistic base of political discourse. It offers a theoretical model of the imbalance of power in human interaction from language communication to socio-political relations. It uses the basic principles of social semiotics to create a match between sociolinguistics and political science. The structural "semiology" of Ferdinand de Saussure and Roland Barthes' and Levi-Strauss' "myth" theories are referred to in support of the idea that human collective psychology is regularly manipulated by politically-based ideological narratives that "go without saying". In the movement "out" of the structuralist binary oppositions between "right" and "wrong", Derrida's post-structural "deconstruction" contributes to the critique of western liberal democracy as regards "equality" and communal knowledge about the political truth.The book will appeal to researchers and university students of both linguistics and political science, as well as specialists in philosophy of language, philosophy of politics, communication theory and social psychology.--